The Effect of Training, Motivation and Incentives on Employee Performance at PT. BFI Finance Indonesia TBK. South Tangerang City - Haryoto, Cecep; Husainah, Nazifah; Nurhayati, Nurhayati; Hasanah, Hasanah (Jurnal Ilmiah Sumber Daya Manusia, 2023)
This study aims to examine and analyze the Effect of Training, Motivation, and Incentives on Employee Performance at PT. BFI Finance Indonesia Tbk, South Tangerang City. The independent variables used are training, motivation and incentives, while the dependent variable is employee performance. The data collection method in this study was carried out by distributing questionnaires to 63 respondents to employees of PT. BFI Finance Indonesia Tbk, South Tangerang City. The research method used is an associative quantitative method using primary data. These results indicate that training has a positive and significant effect on employee performance with a calculated t value greater than t table 2.119 > 1.670 and a significant value of 0.038 < 0.05, motivation has a positive and significant effect on employee performance with a t-count value greater than t-table 2.408 > 1.670 and a significant value of 0.019 <0.05, incentives have a positive and significant effect on employee performance with a t-count value greater than t table 2.385 > 1.670 and significant value 0.020 <0.05. Taken together training, motivation and incentives have a significant effect on employee performance with a calculated F value greater than F table 24.295 > 2.76 and a significant value of 0.00 <0.05.